Sludge dewaterability by dual conditioning using Fenton's reagent with Moringa oleifera. Issue 1 (February 2019) - Faye, Marie Christine Amie Sene; Zhang, Kai Kai; Peng, Sun; Zhang, Yanrong
Highlights: Disintegration of the sludge flocs by Fenton, neutralization and agregation of EPS by Moringa oleifera are the conditioners mechanisms. The reduction of the water content by Fenton and the increase of the particle size by Moringa oleifera improving sludge dewaterability. The combination of Fenton with Moringa oleifera is an interesting perspective for sludge dewaterability. Abstract: The specific resistance to filtration (SRF), sludge cake water content, bound water content, extracellular polymeric substances (EPS) content, particle size, and microstructure of the flocs were measured to evaluate the efficiency of the combined treatment of Moringa oleifera (MO) with Fenton for sludge dewaterability. Results showed that the water content of the sludge cake was reduced from 73.86 to 62% when the dosages of Fe 2+, H2 O2, and MO were 31.93, 22.87, and 800 mg/g TS, respectively. The Fenton- Moringa conditioned sludge (FMCS) presented a better dewaterability than that derived from the solo application of MO or Fenton, with the SRF closely correlating with the EPS central liquor (CL-EPS; R 2 = 0.62), the light bound EPS (LB-EPS; R 2 = 0.55) and the tight bound EPS (TB-EPS;R 2 = -0.83). Moreover, the protein content of LB-EPS and TB-EPS in conditioned sludge showed a strong positive correlation with SRF (R 2 = -0.79 with LB-EPS and R 2 = 0.91 with TB-EPS). The zeta potential further displayed a strong correlation with SRF (R 2 = 0.83). Under Fenton- Moringa conditioning, the particle size of the sludge did not show a significant correlation with SRF (R 2 =-0.20); however, there was a significant correlation between the particle size and the zeta potential (R 2 = 0.56). The observed particle size was larger than that of Fenton conditioned sludge, allowing a better settling of the sludge particles. Furthermore, the microstructure of the FMCS also showed a more porous structure. While Fenton reduces the water content in sludge by disintegrating flocs, MO increases the particle size, neutralizes and aggregates the EPS, hence improving sludge dewaterability and rendering Fenton- MO attractive for sludge treatment.